Calculer les expressions suivantes :
A
= -3 + 5 - 2 + 1 ; B
= 5 - 4 + 2 - 6 ; C
= 2 - 6 - 4 + 3 ;
D
= -6 + 5 - 4 + 3 - 2 - 1 + 7 ;
E
= 2 - 6 + 4 - 5 - 3 - 2 - 4 + 6 - 10 ;
F
= (+3) - (+2) - (-3) + (-4) + (+6) ;
G
= (-2) + (-5) - (-6) + (+7) - (+3) ;
H
= - (-2) + (-4) - (-6) + (-2) - (+3) ;
I = (-1) + (-1) - (+1) + (-1) - (+1) ;
J = (-12) + (-6) - 4 - (-10) + (+5) ;
K
= 5 - (-3) - 4 + (-6) - (+7).

1

Réponses

2014-10-13T01:45:57+02:00
A=1
B=-3
C=-5
D=2
E=-18
F=6
G=3
H=-1
I=-5
J=-7
K=-9
tu n'as pas détailler
tu as mis directement le résultat
ta réponse est incomplete